Peer Engagement Toolkit and Guidelines - Kelly, Peter; O'Neill, Debra; O'Hara, Andy (Trinity Colle Dublin, UISCE, 2024)
The production of this toolkit is part of the recommendations of a Community Participation Research Project which was undertaken by Trinity College Dublin in partnership with UISCE in the Summer of 2024. The project was born out of the fact that although the current National Drug Strategy places a strong emphasis on clients involvement, the experiences of PWUD accessing services showed evidence to the contrary. The literature confirms that many PWUD still experience institutional stigma and have endured discrimination through their experiences of treatment services (Mayock and Butler, 2021, Comiskey, 2021). This evidence was also confirmed in the findings from the Knowledge Exchange Workshop (KEW) which was also conducted as part of the above research report. The Union for Improved Services Communication and Education [UISCE] has been involved in several initiatives that have increased the level of participation by PWUD. These initiatives have included research, policy and service development, and health promotion interventions including outreach overdose prevention. As well as raising the profile of PWUD in Ireland, through this work, UISCE has set a range of clear strategic goals to improve the lives of PWUD across several domains (UISCE, 2022). While UISCE’s strategy is extremely welcome, on exploration there is little guidance or evidence available on how the process of peer engagement itself can be operationalised. This toolkit therefore provides a mechanism for both service providers and PWUD’s themselves, to identify the level of participation they are operating at. The toolkit also provides directions on how to progress to higher levels of engagement. The evidence suggests that engagement and participation can range from non-participation/tokenism towards full partnership and control (Arnstein, 1969). This toolkit, informed by the research findings of “Development of Guidelines to Support Peer Led Engagement in Ireland” (Kelly et al., 2024) provides general guidelines and a conceptual framework that is accessible and implementable on a practical level.
Keywords: Inclusive Society; Addiction and substance abuse; Health status and inequalities; Nursing; Public health; Mental Health/Psychosocial disability; Health; Policy; Social exclusion